A De Novo Mosaic PHEX Variant Causing Sporadic X-Linked Hypophosphatemic Rickets in a 2-Year-Old Girl - Poon, Kok-Siong; Tan, Karen Mei-Ling; Zacharin, Margaret; Ho, Cindy Wei-Li (Journal of Pediatric Genetics, 2021)
Pathogenic variants in the PHEX gene are causative of X-linked hypophosphatemic rickets (XLH). We present a case of a 2-year-old girl with hypophosphatemic rickets with genu varum and short stature without any family history of XLH. Next generation sequencing of the PHEX gene identified a splice donor variant, NM_000444.6:c.1173 + 5G > A in intron 10. This variant had a mosaic pattern with only 22% of the sequence reads showing the variant allele and was not present in the girl's parents, both of whom had a normal phenotype. This is a sporadic case of a de novo mosaic splice-site variant in the PHEX gene.
Keywords: PHEX; X-linked hypophosphatemic rickets; mosaic